NUCLEAR-POWERED STIRLING ENGINES IN ELECTRIC POWER GENERATION PLANTS - SUNDARAM, V.S.SHAI; YOGARAJ, S.; ANAND, S.; DEVANDIRAN, E. (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
Power generation in a large scale is of vital importance considering the huge population of our country as well as the technological advances in manufacturing various electronic gadgets. The paper starts with the elementary ideas that underline the working of a nuclear power plant and builds up to clear explanations of how Stirling engines can replace steam turbines by simplifying the plant to yield greater efficiency in terms of power generated and providing a pristine environment by reducing radioactive byproducts. The paper also focuses on the configurations, operations and merits of Stirling engines over the conventional steam turbines